Bridging yield gaps in rice production through integrated crop and nutrient management with farmer groups - Sembiring, Hasil; Girsang, Setia Sari; Anshori, Arif; Erythrina, Erythrina; Susilawati, Pepi Nur; Bhermana, Andy; Ngongo, Yohanis; Hanapi, Sidiq; Prawiranegara, Darojat; Subekti, Nuning A.; Sasmita, Priatna; Pabuayon, Irish Lorraine B.; et al. (Elsevier, 2025)
"Context or problem Studies have shown that rice yields in Asia can be further increased, but achieving higher yields with high efficiencies of resource use will require the development and use of management practices customized to reduce the specific yield-limiting constraints of farmers. Objective or research question We hypothesized that farmers’ yields could be increased to an attainable target through participation of technical experts with farmer groups to identify and implement a group-specific integrated crop and nutrient management practice (ICNM), which combined an improved rice variety, optimum population of transplanted rice, and one site-specific nutrient management (SSNM) practice designed to achieve sufficient spikelets for the target yield. Methods The ICNM of one farmer group was compared to the farmer’s management practices (FMP) of an adjacent farmer group at three locations with irrigated rice, two locations with rainfed lowland rice, and two locations in rainfed tidal swamps in Indonesia. Each group had 14–55 farmers. Yield gaps were estimated from the difference between yield potential — simulated using actual weather conditions at each location — and the yield measured for each farmer. Results The FMP yields averaged 63–69 % of yield potential for IR 64 at irrigated locations and 53–60 % of water-limited yield potential for IR 64 at rainfed locations. The ICNM increased yield compared to FMP by about 20 % at each location, largely through an increase in panicles and spikelets per panicle. With ICNM, > 40 % of farmers attained ≥ 80 % of yield potential at each irrigated location and > 40 % of farmers attained ≥ 70 % of the water-limited yield potential at three of the four rainfed locations. The ICNM increased costs for fertilizer, seed, nursery management, and transplanting by an average sum total of USD 53 ha–1, but ICNM reduced use of insecticide and fungicide. With ICNM, pesticide use was reduced by an average of two applications resulting in an average savings of USD 23 ha–1. The ICNM reduced yield-scaled costs, and the added net benefit with ICNM averaged 307 USD ha–1. Conclusions One SSNM practice — agreed upon by a farmer group and then used by farmers in the group — combined with an adapted rice variety and adequate plant population increased yield and income, while achieving for many of the farmers a targeted fraction of simulated yield potential. Implications or significance The participatory development with a farmer group of one group-specific ICNM practice and the subsequent use of the ICNM practice by members in the farmer group provides a promising approach for closing yield gaps in Asian rice production.